2009
DOI: 10.1093/nar/gkn864
|View full text |Cite
|
Sign up to set email alerts
|

Bionemo: molecular information on biodegradation metabolism

Abstract: Bionemo (http://bionemo.bioinfo.cnio.es) stores manually curated information about proteins and genes directly implicated in the Biodegradation metabolism. When possible, the database includes information on sequence, domains and structures for proteins; and sequence, regulatory elements and transcription units for genes. Thus, Bionemo is a unique resource that complements other biodegradation databases such as the University of Minessota Biocatalysis/Biodegradation Database, or Metarouter, which focus more on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Bionemo (http:// bionemo.bioinfo.cnio.es) is a database that includes structural information on proteins, regulatory elements, genes, etc. This database supports the aforementioned databases in a way that it provides regulatory perspective to the biochemical aspects of biodegradation [89].…”
Section: Desired Community and Its Performancementioning
confidence: 62%
“…Bionemo (http:// bionemo.bioinfo.cnio.es) is a database that includes structural information on proteins, regulatory elements, genes, etc. This database supports the aforementioned databases in a way that it provides regulatory perspective to the biochemical aspects of biodegradation [89].…”
Section: Desired Community and Its Performancementioning
confidence: 62%
“…Because the activity of the dioxygenase seems to be impervious to DNT whether DntR is present or not we concluded that (i) the regulator DntR does not stimulate directly or indirectly the first step of the DNT degradation, (ii) DNT does not control in any other way (e.g. riboswitches) expression of the genes that encode the leading biodegradation step and (iii) DntR does not repress either the P DNT promoter in the presence or absence of DNT, as is the case in other LysR‐type regulators when the inducer is missing (Maddocks and Oyston, 2008; Carbajosa et al ., 2009). While many TFs gratuitously respond to unrelated inducers (de Lorenzo and Perez‐Martin, 1996; Carbajosa et al ., 2009), that the regulatory system just examined allowed expression of the dntA genes independently of DNT presence suggested the second regulatory scenario discussed above i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The list of chemically inducible TFs that can be exploited to the same or similar ends is very large (114,115) and likely to be expanded in the near future. An added bonus of these expression systems is that owing to being encoded by promiscuous plasmids, they are likely to be operative in a large variety of hosts.…”
Section: Expression Systemsmentioning
confidence: 99%